PERANCANGAN VIDEO ANIMASI 2D “OPERASI HITUNG” MENGGUNAKAN TEKNIK MOTION GRAPHIC SEBAGAI MEDIA PEMBELAJARAN - Rohadi, Alifia Diwi Maulidya (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2022)
The use of instructional media that is still manual as well as students' limitations in understanding the material and the lack of student motivation in learning causes teachers difficulties in delivering learning material. This needs to be developed, especially in appropriate 2-dimensional animation learning media which must be the main key so that students can follow learning well and increase student motivation in learning. Teaching modes in class, one of which is video animation. The process of learning arithmetic operations will be more easily understood by students if presented with detailed explanations and examples. According to the Computing Research and Computer Technology Research Institute (CTR), people remember 80% better what they see, hear, and do. This study aims to support the student learning process and make it easier for them to capture learning because it is animated and also equipped with detailed information. This research is motivated by a lack of understanding of the concept of arithmetic operations. Animations are made using Kinemaster as one of the main applications of motion graphics technology in the animation process and using FlipaClip as one of the 2D technology applications in the animation process.